Ocena ryzyka inwestowania w walory wybranych spółek branży budowlanej notowanych na GPW w Warszawie: Assessment of the risks of investing in securities of selected construction companies listed on the WSE in Warsaw - Kruk, Marta (Management and Administration Journal, 2021)
Every action or choice is subject to certain risks. When making decisions on taking or withdrawing from actions one anticipates certain results in the future, but never can be sure how different factors will influence the effects of the decisions taken. Taking into consideration that the conditions in the future are shaped by a huge number of factors affecting them, as well as complex processes and their variability, we cannot predict the future. Then there is the risk that the planned action or condition will not be met. This paper presents an assessment of the risks of investing in securities of selected companies in the construction industry.